Pendidikan Karakter Religius Melalui Kesenian Hadrah di Era Modernisasi - Nofroza Yelli; Akhmado Naldito (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe the role of Hadrah art as a medium for religious character education in the era of modernization, using the Hadrah Community of Talang Kedondong in Palembang as a case study. Religious character education is crucial in shaping a young generation that is devout and of noble character; however, it faces serious challenges due to modernization and the development of digital technology, which are shifting the younger generation’s interest away from traditional arts. The research method employed is qualitative with a case study approach. Data collection techniques include participatory observation, in-depth interviews with the community founder, administrators, members, and the surrounding community, as well as documentation. The results indicate that Hadrah art remains viable and functions as a medium for religious character education through regular practice, its social and religious roles within the community, and its adaptation to modernization without abandoning traditional values. Supporting factors include community support, a sense of family, and religious values, while inhibiting factors include a lack of interest among the younger generation, the influence of gadgets, and unstable member commitment. The novelty of this study lies in the integration of the concept of religious character education into the analysis of the existence of Hadrah art.